Towards a transformative governance of the Amazon - Pereira, J. C.; Terrenas, J. (Global Policy, 2022)
The crises of the Anthropocene can neither be confronted incrementally nor through short-term, reductionist strategies. As the risk of severe, irreversible socioecological damage increases, transformative change towards achieving long-term sustainability becomes ever-pressing. Against this backdrop, we explore how transformative governance can help strengthen ecosystem resilience, empower vulnerable communities and ensure sustainable development in the Amazon. The article starts by briefly reviewing the concept of transformative governance, arguing that it provides an adequate framework for thinking about and responding to the challenges of the Anthropocene. It then looks at how extant governance practices are destroying and fragmenting the Amazon, eroding the resilience of regional ecosystems. It proceeds by investigating how the Andes–Amazon–Atlantic Corridor, a transnational project aligned with the normative commitments and operational principles of transformative governance, aimed at protecting, restoring and building socioecological connectivity in the region, can offer an alternative pathway for Amazonian development in the new geological epoch.